Signaling pathways of oxidative stress response: the potential therapeutic targets in gastric cancer - Liu, Yingying; Shi, Yu; Han, Ruiqin; Liu, Chaoge; Qin, Xiaogang; Li, Pengfei; Gu, Renjun (Frontiers in Immunology, 2023)
Gastric cancer is one of the top causes of cancer-related death globally. Although novel treatment strategies have been developed, attempts to eradicate gastric cancer have been proven insufficient. Oxidative stress is continually produced and continually present in the human body. Increasing evidences show that oxidative stress contributes significantly to the development of gastric cancer, either through initiation, promotion, and progression of cancer cells or causing cell death. As a result, the purpose of this article is to review the role of oxidative stress response and the subsequent signaling pathways as well as potential oxidative stress-related therapeutic targets in gastric cancer. Understanding the pathophysiology of gastric cancer and developing new therapies for gastric cancer depends on more researches focusing on the potential contributors to oxidative stress and gastric carcinogenesis.